A Replication by Any Other Name: A Systematic Review of Replicative Intervention Studies. (July 2016) - Cook, Bryan G.; Collins, Lauren W.; Cook, Sara C.; Cook, Lysandra
Replication research is essential to scientific knowledge. Reviews of replication studies often electronically search for replicat * as a textword, which does not identify studies that replicate previous research but do not self-identify as such. We examined whether the 83 intervention studies published in six non-categorical research journals in special education in 2013 and 2014 might be considered replications regardless of using the term replicat * by applying criteria related to (a) the stated purpose of the study and (b) comparing the findings of the study with the results of previous studies. We coded 26 intervention studies as replications. Authors of 17 of these studies reported that their findings solely agreed with the results of the original study(ies). Author overlap occurred for half of the replicative studies. The likelihood of findings being reproduced did not vary as a function of author overlap. We discuss implications and recommendations based on these findings.